1976
DOI: 10.1017/s0043174500066510
|View full text |Cite
|
Sign up to set email alerts
|

Tall Morningglory Response to Planting Depth

Abstract: Emergence of tall morningglory [Ipomoea purpurea(L.) Roth] seedlings was delayed and reduced as planting depths increased from 1.3 to 5.0 cm. Development of seedlings emerging from 3.8 cm or greater depth was delayed for up to 4 weeks as indicated by dry weight accumulation. In both greenhouse and field studies, chemical control of tall morningglory was generally greater when seedlings emerged from planting depths of 2.5 cm or greater. The competitive ability of tall morningglory, as indicated by yield reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

1978
1978
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 8 publications
(10 reference statements)
2
9
1
Order By: Relevance
“…Germination beyond 7 DAS was limited to 8 and 3% germination at a 10-cm depth 14 DAS and at 0.5 cm depth 21 DAS, respectively (data not shown). These results were similar to the results obtained by Cole (1976) and Wilson and Cole (1966). Both studies reported that tall morningglory emergence was delayed and reduced as planting depths increased from 1.3 to 5.0 cm.…”
Section: Resultssupporting
confidence: 91%
“…Germination beyond 7 DAS was limited to 8 and 3% germination at a 10-cm depth 14 DAS and at 0.5 cm depth 21 DAS, respectively (data not shown). These results were similar to the results obtained by Cole (1976) and Wilson and Cole (1966). Both studies reported that tall morningglory emergence was delayed and reduced as planting depths increased from 1.3 to 5.0 cm.…”
Section: Resultssupporting
confidence: 91%
“…Unlike our results, Cole (1976) observed that emergence of tall morningglory seedlings was delayed and Table 4. Student evaluation of the depth of emergence experiment and scientific paper assignment.…”
Section: Resultscontrasting
confidence: 99%
“…This is below the zone of the herbicide -treated soil in most instances. In addition, Cole (3) found that morningglory seedlings emerging from depths of 4 em or greater were delayed by as much as 4 weeks, compared to those emerging from a shallower depth. Soil-applied herbicides must have sufficient residual activity to control these lateemerging weeds.…”
Section: Introductionmentioning
confidence: 99%